Assessment of Changes in Concentration of Total Antioxidant Status, Acute-Phase Protein, and Prolactin in Patients with Osteoarthritis Subjected to a Complex Spa Treatment with Radon Water: Preliminary Results. (23rd April 2020) - Kuciel-Lewandowska, Jadwiga; Kasperczak, Michał; Pawlik-Sobecka, Lilla; Paprocka-Borowicz, Małgorzata; Gnus, Jan
Abstract : Spa treatment brings many clinical benefits such as improved physical activity, pain relief, and improved quality of life. In the literature, there are only few objective studies evaluating changes in metabolism possibly influencing clinical outcomes. The main purpose of our study was the assessment of the effect of spa treatment on changes in concentration of TAS, CRP, and PRL in patients with osteoarthritis. Patients receiving spa treatment were enrolled. TAS, CRP, and PRL levels were obtained using standard tests before the beginning of treatment as well as on days 5 and 18. The study group consisted of n = 35 patients with peripheral joint and spinal osteoarthritis. The control group consisted of 15 people selected from the resort staff, who also suffered from osteoarthritis and had no contact with radon. An increase in TAS concentration was found in the study group following therapy while the control group was characterized by a significant decrease in TAS. On day 5, an increase in TAS concentration was found in both groups, however, with much worse result in the control group. No changes in CRP concentration were statistically significant. PRL concentration was proven to decrease in a statistically significant way after treatment in the study group. This trial is registered with NCT03274128 .